Climate Extreme Indices Derived from Observed Daily Temperature Data Over Three Cities of Thrace Region, Turkey - Sertaç Oruç (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Construction industry can be affected by climate change in particular temperature and temperature extremes not only for the design phase but also for production or end-use/operation phases. In this regard the major climatic factors that are dominant for the building lifecycle must be evaluated. This study determined the 13-sector specific ET-SCI temperature indices annually and investigated their trend characteristics at Edirne, Kırklareli and Tekirdağ of Thrace Region for the historical period. The results showed a dominant increasing temperature trend over the region. Edirne, Kırklareli, and Tekirdağ stations showed significantly increasing trends for the hottest night, average daily maximum, and average daily minimum temperature indices in this study. Furthermore, the hottest day index also showed an increasing trend for all the stations with a significant trend for Edirne and Tekirdağ. Moreover, significant decreasing trends were observed in the heating degree days and increasing significant trends were observed for the SU (summer days), CDDCOLD18 (cooling degree days) and TR (tropical nights) values at all the stations.